1980
DOI: 10.1007/bf00007429
|View full text |Cite
|
Sign up to set email alerts
|

Protozoan species accrual on artificial islands in differing lentic and wetland systems

Abstract: In the recently broadened context of insular biogeographic theory, artificial substrates might well be considered as initially barren islands with the surrounding natural community acting as a source pool of potential colonists. In an attempt to relate protozoan communities forming on polyurethane foam (PF) substrates to their environments, a series of field experiments were performed in several aquatic and semi-aquatic (wetlands) systems in Michigan, Virginia, and Colorado. Results were considered in the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…2). PFU samples were harvested at time intervals of 1, 3, 6, 9, 14 days, respectively during the periods of exposure in water, Plafkin et al 7 having demonstrated that species numbers show negligible increase after this time interval. Each time, two PFU blocks were collected as parallel samples for analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). PFU samples were harvested at time intervals of 1, 3, 6, 9, 14 days, respectively during the periods of exposure in water, Plafkin et al 7 having demonstrated that species numbers show negligible increase after this time interval. Each time, two PFU blocks were collected as parallel samples for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…4,5 Structural and functional characteristics of entire communities of organisms have been found to be much more reliable for evaluating environmental conditions. 2,[5][6][7][8][9][10][11] Protozoans, which usually are considered to include autotrophic and heterotrophic flagellates, amoebae and ciliates, are important and integral components of aquatic ecosystems. These organisms play a key role in energy flow and mineral cycling in aquatic food webs.…”
Section: Introductionmentioning
confidence: 99%
“…The comparison of species-abundance data among communities from differing environments is a potentially valuable procedure (Patrick, 1968(Patrick, , 1971(Patrick, , 1975Cairns et al, 1972Cairns et al, , 1979Southwood, 1978 ;Plafkin et al, 1980) . Taylor et al (1976) have proposed the use of species-abundance relationships as indicators of environmental stability .…”
Section: Introductionmentioning
confidence: 99%
“…Colonization of substrates in the upper portion of the water column of the polluted harbor a t Waukegan (station W2) appeared to be more stimulated by higher nutrient levels than inhibited by toxic materials that might be leaching from the sediments. Previous studies have 16/ROSS AND HENEBRY shown that artificial substrates in nutrient-poor, relatively unproductive (oligotrophic) lakes are colonized a t slower rates but reach ultimately higher numbers of protozoan species than in nutrient-rich, relatively productive (eutrophic) waters (Plafkin et al, 1980;Henebry and Cairns 1984;. If colonization had been monitored for a longer time, more species may have accumulated on PF substrates in South Harbor (station W3).…”
Section: In Situ Testsmentioning
confidence: 99%